К вопросу о технологической подготовке бакалавра библиотечно-информационной деятельности (Библиосфера, 2011)
The article deals with the questions of sufficient back-up of professional competence of bachelors in library science that is formed during educational process, particularly professional, technological and analytical skills that are necessary for the future librarians.